Установка для получения CO[2]-экстрактов - Гаврилов П. М. Петр Михайлович; Ревенко Ю. Н. Юрий Александрович; Бараков Б. Н. Борис Николаевич; Бондин В. В. Владимир Викторович; Бычков С. И. Сергей Иванович; Рыбалкин И. А. Игорь Андреевич
опубл. 20.07.10